How does coronary stent implantation impact on the status of the microcirculation during primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction? - De Maria, G; Cuculi, F; Patel, N; Channon, K; Banning, A; al., E (Oxford University Press, 2015)
Primary percutaneous coronary intervention (PPCI) is the optimal treatment for patients presenting with ST-elevation myocardial infarction (STEMI). An elevated index of microcirculatory resistance (IMR) reflects microvascular function and when measured after PPCI, it can predict an adverse clinical outcome. We measured coronary microvascular function in STEMI patients and compared sequential changes before and after stent implantation.In 85 STEMI patients, fractional flow reserve, coronary flow reserve, and IMR were measured using a pressure wire (Certus, St Jude Medical, St Paul, MN, USA) immediately before and after stent implantation. Stenting significantly improved all of the measured parameters of coronary physiology including IMR from 67.7 [interquartile range (IQR): 56.2-95.8] to 36.7 (IQR: 22.7-59.5), P < 0.001. However, after stenting, IMR remained elevated (>40) in 28 (32.9%) patients. In 15 of these patients (17.6% of the cohort), only a partial reduction in IMR occurred and these patients were more likely to be late presenters (pain to wire time >6 h). The extent of jeopardized myocardium [standardized beta: -0.26 (IMR unit/Bypass Angioplasty Revascularization Investigation score unit), P: 0.009] and pre-stenting IMR [standardized beta: -0.34 (IMR unit), P: 0.001] predicted a reduction in IMR after stenting (ΔIMR = post-stenting IMR - pre-stenting IMR), whereas thrombotic burden [standardized beta: 0.24 (IMR unit/thrombus score unit), P: 0.01] and deployed stent volume [standardized beta: 0.26 (IMR unit/mm(3) of stent), P: 0.01] were associated with a potentially deleterious increase in IMR.Improved perfusion of the myocardium by stent deployment during PPCI is not universal. The causes of impaired microvascular function at the completion of PPCI treatment are heterogeneous, but can reflect a later clinical presentation and/or the location and extent of the thrombotic burden.